(untitled) (Terr@ Plural, 2022)
Linear erosion is one of the types of water erosion that cause the most environmental problems due to the concentration of water flows that has great potential for land degradation. This work aims to identify areas of eroded soil that occur in the Paraíso River Watershed using free geotechnologies through the vectorization of erosion identified through the analysis of high spatial resolution satellite images freely available on the Google Earth platform. The results obtained point out that in the Paraíso River watershed most of the linear erosions are furrow-type features, the mildest form of this type of erosive process. A total of 463 erosion axes were identified, composed of furrows, ravines, and gullies. The temporal monitoring of images has elucidated the origin of the silting identified in a stretch of the Paraíso River near the MS-316 highway. Thus, the availability of high spatial resolution satellite images associated with the resources available for processing spatial data makes it possible to analyze extensive areas and identify erosive processes with greater agility, helping to identify the measures to be adopted to contain and/or recover the sites affected by this environmental problem.